Effectiveness of an immersive virtual reality environment on curricular training for complex cognitive skills in liver surgery: a multicentric crossover randomized trial. Issue 12 (December 2022) - Rashidian, Nikdokht; Giglio, Mariano C.; Van Herzeele, Isabelle; Smeets, Peter; Morise, Zenichi; Alseidi, Adnan; Troisi, Roberto I.; Willaert, Wouter
Abstract: Background: Virtual reality (VR) is increasingly used in surgical education, but evidence of its benefits in complex cognitive training compared to conventional 3-dimensional (3D) visualization methods is lacking. The objective of this study is to assess the impact of 3D liver models rendered visible by VR or desktop interfaces (DIs) on residents' performance in clinical decision-making. Method: From September 2020 to April 2021, a single-blinded, crossover randomized educational intervention trial was conducted at two university hospitals in Belgium and Italy. A proficiency-based stepwise curriculum for preoperative liver surgery planning was developed for general surgery residents. After completing the training, residents were randomized in one of two assessment sequences to evaluate ten real clinical scenarios. Results: Among the 50 participants, 46 (23 juniors/23 seniors) completed the training and were randomized. Forty residents (86.96%) achieved proficiency in decision-making. The accuracy of virtual surgical planning using VR was higher than that using DI in both groups A (8.43 ± 1.03 vs 6.86 ± 1.79, p < 0.001) and B (8.08 ± 0.9 vs 6.52 ± 1.37, p < 0.001). Conclusion: Proficiency-based curricular training for liver surgery planning successfully resulted in the acquisition of complex cognitive skills. VR was superior to DI visualization of 3D models in decision-making. Clinicaltrials.gov id: NCT04959630.